Generalized Kantorovich Operators on Bauer Simplices and Their Limit Semigroups. (3rd June 2017) - Cappelletti-Montano, Mirella; Leonessa, Vita
ABSTRACT: In this paper, we prove an asymptotic formula for generalized Kantorovich operators associated with the canonical Markov projection on a given Bauer simplex K . That formula involves an operator acting on the subalgebra of all products of aﬃne functions on K . Moreover, we prove that such an operator is closable and its closure is the generator of a Markov semigroup which, in turn, may be represented in terms of iterates of the above-mentioned generalized Kantorovich operators.